Tindak Pidana Kesusilaan dalam KUHP 2023: Perspektif Kelompok Agama Minoritas - Nella Sumika Putri (Jurnal HAM, 2025)
Indonesia, a nation celebrated for its rich diversity of ethnicities and religions, embodies a societal pluralism that deeply influences perceptions of morality and acceptable behaviour. The enactment of the 2023 Criminal Code reflects these complexities, particularly in its use of "moral policing" to redefine adultery and criminalize cohabitation as moral offenses. These provisions were integrated into contentious articles during the Code's drafting and discussion phases, sparking significant debate. Proponents claim that the existence of these moral transgressions is consistent with Indonesian society's moral and religious values. Conversely, opponents argue that these provisions as an overreach by the state, infringing upon personal freedoms and disproportionately affecting religious minorities whose beliefs and practices may diverge from the majority. Adultery and cohabitation, the focal points of these provisions, are intrinsically linked to the institution of marriage. In Indonesia, marriage transcends its administrative role and is deeply embedded within religious and cultural traditions. This dual significance renders the issue particularly contentious, as interpretations of marriage vary widely across the country's diverse communities. The ambiguity surrounding the definition of "marriage" within the legal framework raises concerns about potential discrimination. Minority religious groups, particularly those whose marital practices are not formally recognized or registered, may find themselves vulnerable to legal repercussions under the adultery and cohabitation clauses.  This article seeks to delve into the nuanced effects of these regulations, focusing on their potential to disproportionately affect religious minorities and the broader question of balancing societal norms with individual liberties in a diverse nation.